Effect of long-term remote ischemic conditioning on inflammation and cardiac remodeling. (4th July 2019) - Pryds, Kasper; Rahbek Schmidt, Michael; Bjerre, Mette; Thiel, Steffen; Refsgaard, Jens; Bøtker, Hans Erik; Drage Østgård, René; Ranghøj Nielsen, Roni
Abstract: Background. Remote ischemic conditioning (RIC) protects against acute ischemia-reperfusion injury and may have beneficial effects in patients with stable cardiovascular disease. We investigated the effect of long-term RIC treatment in patients with chronic ischemic heart failure (CIHF). Methods. Prespecified post-hoc analysis of a prospective, exploratory and outcome-assessor blinded study. Twenty-one patients with compensated CIHF and 21 matched controls without heart failure or ischemic heart disease were treated with RIC once daily for 28 ± 4 days. RIC was conducted as 4 cycles of 5 minutes upper arm ischemia followed by 5 minutes of reperfusion. We evaluated circulating markers of inflammation and cardiac remodeling at baseline and following long-term RIC. Results. RIC reduced C-reactive protein from 1.5 (0.6–2.5) to 1.3 (0.6–2.1) mg/l following long-term RIC treatment ( p = .02) and calprotectin from 477 (95% CI 380 to 600) to 434 (95% CI 354 to 533) ng/ml ( p = .03) in patients with CIHF, but not in matched controls. Overall, RIC did not affect circulating markers related to adaptive or innate immunology or cardiac remodeling in patients with CIHF. Among patients with CIHF and N-terminal pro-brain natriuretic peptide (NT-proBNP) plasma levels above the geometric mean of 372 ng/l, long-term RIC treatment reduced soluble ST2 ( n = 9) from 22.0 ± 3.7 to 20.3 ± 3.9 ng/ml following long-term RIC treatment ( p = .01). Conclusion . Our findings suggest that long-term RIC treatment has mild anti-inflammatory effects in patients with compensated CIHF and anti-remodeling effects in those with increased NT-proBNP levels. This should be further investigated in a randomized sham-controlled trial.